Transformation of Candra Kirana as a beautiful princess into Panji Semirang; An invincible hero - Mu’jizah, Mu’jizah; Ikram, Achadiati (Wacana, Journal of the Humanities of Indonesia, 2020)
The Malay Panji romance comes in many versions, one of which is the Hikayat Panji Semirang whose principal character is Candra Kirana, Panji’s betrothed. The story describes Candra Kirana as a woman in the guise of a man doing a man’s job. It has produced a number of new creations in the form of popular stories, novels, films, and comics. This article aims to present a description of a woman possessed of superlative qualities, once supposedly possessed only by men. The method used in the analysis is the gender approach. This research focuses on the text of Hikayat Panji Semirang Br. 126 in the collection of the National Library, Jakarta. The research shows a story which diverges from other versions, namely: the murder by black magic of the queen by the concubine, causing Candra Kirana to leave the palace and establish a kingdom of her own, Mataun. During her wanderings she becomes a gambuh player.